SYSTEMATIC LITERATURE REVIEW ON AGILE FACTORS IN CREATING LEARNING ENVIRONMENT THAT PROMOTES SUSTAINABLE SOFTWARE ENGINEERING COMPETENCIES - Mannir Bello; Dayang N. A. Jawawi; Adila Firdaus Arbain (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In today’s ever evolving and dynamic society, lifelong learning and software engineering competency for sustainable development are essential. In current contemporary society, modern instructional materials and frameworks must be employed to assist the transmission of important qualities such as adaptability, creativity, systemic thinking, responsibility, and uncertainty management. Given its deep roots in participative, collaborative, and constructionist ideas, Agile frameworks, which are becoming increasingly popular for project management across several industries, might serve as an effective instrument for conveying these competencies. This paper carries out a systematic literature review to analyse how this modern pedagogical tool will be used to encourage crucial sustainable undergraduate software engineering competencies in the field of software engineering. We employed a systematic literature review methodology in this work. To help researchers conduct systematic reviews, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) is a robust framework. It goes beyond what is typically included in ordinary literature reviews, which are essentially summaries of earlier research on a particular topic. The time frame of our research is 2019–2024. The biggest database for reliable scholarly papers, Scopus, was searched. After the publications were filtered using the exclusion criteria, 49 eligible papers were chosen for review. Based on the study, twenty-five (25) factors were found, that are useful in communicating competencies. These include strong leadership, team autonomy, collaborative organizational culture, team competency, and sustainable software design. Other Agile factors include code quality, scalability, maintainability, and continuous attention to technical excellence. The software engineering department, instructors and students needs to consider the factors for sustainable undergraduate software engineering competency. It showed that Agile factors assist to create learning environment that produce reliable and sustainable undergraduate’s software engineering while raising instructors and students’ motivation, performance, and satisfaction.